2015
DOI: 10.1109/tim.2014.2355653
|View full text |Cite
|
Sign up to set email alerts
|

On-line Sizing of Pneumatically Conveyed Particles Through Acoustic Emission Detection and Signal Analysis

Abstract: Accurate measurement of the particle size distribution of pneumatically conveyed pulverized fuel is critical to achieving optimal combustion efficiency and minimum pollutant emissions at coal and biomass-fired power plants. This paper presents a prototype instrumentation system for the on-line continuous measurement of particle size distribution through acoustic emission (AE) detection. The proposed method extracts particle size information from the impulsive AE signals arising from impacts of particles with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Accurate measurements of the contact time are not only important in the basic studies of contact mechanisms in order to assess the validity of the proposed theory [2], [3], they are also important in a wide range of different applications related to, for example, contact mechanics, tribology, shot peening, wear, erosion, rock falls, military ballistics, measurements of hardness at high strain rates and granular matter research. Due to its linear dependence on the radius, the contact time of spherical particles impacting thick plates is, for instance, a good criterion for their size [4], [5], [6], [7], [8] whereas particle sizing is an important requirement in many areas of industrial processing and manufacture [8]. If the velocity of the particle is known with some uncertainty, the size of the particle can be determined via its impact with another solid more accurately by measuring the contact time than the maximum force [5], [6], [8], because the contact time has a more gentle dependence on the approach velocity as opposed to the maximum force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate measurements of the contact time are not only important in the basic studies of contact mechanisms in order to assess the validity of the proposed theory [2], [3], they are also important in a wide range of different applications related to, for example, contact mechanics, tribology, shot peening, wear, erosion, rock falls, military ballistics, measurements of hardness at high strain rates and granular matter research. Due to its linear dependence on the radius, the contact time of spherical particles impacting thick plates is, for instance, a good criterion for their size [4], [5], [6], [7], [8] whereas particle sizing is an important requirement in many areas of industrial processing and manufacture [8]. If the velocity of the particle is known with some uncertainty, the size of the particle can be determined via its impact with another solid more accurately by measuring the contact time than the maximum force [5], [6], [8], because the contact time has a more gentle dependence on the approach velocity as opposed to the maximum force.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its linear dependence on the radius, the contact time of spherical particles impacting thick plates is, for instance, a good criterion for their size [4], [5], [6], [7], [8] whereas particle sizing is an important requirement in many areas of industrial processing and manufacture [8]. If the velocity of the particle is known with some uncertainty, the size of the particle can be determined via its impact with another solid more accurately by measuring the contact time than the maximum force [5], [6], [8], because the contact time has a more gentle dependence on the approach velocity as opposed to the maximum force. A sphere drop on a stationary plate or a block is also often used as a standard acoustic source of ultrasonic waves.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research has demonstrated that AE, a non-destructive ultrasonic technique, is a reliable predictor of Gaussian PSD [64][65][66][67]. The maximum amplitude of the time-domain AE signal, generated by the collision of a moving particle with a rigid surface, is correlated with particle size to estimate a single descriptor, typically d 50 .…”
Section: Acoustic Emissions Techniquementioning
confidence: 99%
“…A last matter to considering is that owing to the high data rates required to process the AE phenomenon, these advanced methods are computationally expensive, so usually they are implemented under an offline framework (first capturing the data from the survey, to later separating the AE events). Although some efforts has been made in order to implement hardware architectures that can operate under an online approach [18][19][20], strategies that can lead to faster and efficient implementations (this particularly necessary for long surveys), are desirable.…”
Section: Introductionmentioning
confidence: 99%